Cross-Activation of Hemichannels/Gap Junctions and Immunoglobulin-Like Domains in Innate–Adaptive Immune Responses - Meng, Jiang-Hui; Chen, Chang-Xu; Ahmadian, Mohammad R.; Zan, Hong; Luo, Kai-Jun; Jiang, Jean X. (Frontiers in Immunology, 2022)
Hemichannels (HCs)/gap junctions (GJs) and immunoglobulin (Ig)-like domain-containing proteins (IGLDCPs) are involved in the innate–adaptive immune response independently. Despite of available evidence demonstrating the importance of HCs/GJs and IGLDCPs in initiating, implementing, and terminating the entire immune response, our understanding of their mutual interactions in immunological function remains rudimentary. IGLDCPs include immune checkpoint molecules of the immunoglobulin family expressed in T and B lymphocytes, most of which are cluster of differentiation (CD) antigens. They also constitute the principal components of the immunological synapse (IS), which is formed on the cell surface, including the phagocytic synapse, T cell synapse, B cell synapse, and astrocytes–neuronal synapse. During the three stages of the immune response, namely innate immunity, innate–adaptive immunity, and adaptive immunity, HCs/GJs and IGLDCPs are cross-activated during the entire process. The present review summarizes the current understanding of HC-released immune signaling factors that influence IGLDCPs in regulating innate–adaptive immunity. ATP-induced “eat me” signals released by HCs, as well as CD31, CD47, and CD46 “don’t eat me” signaling molecules, trigger initiation of innate immunity, which serves to regulate phagocytosis. Additionally, HC-mediated trogocytosis promotes antigen presentation and amplification. Importantly, HC-mediated CD4+ T lymphocyte activation is critical in the transition of the innate immune response to adaptive immunity. HCs also mediate non-specific transcytosis of antibodies produced by mature B lymphocytes, for instance, IgA transcytosis in ovarian cancer cells, which triggers innate immunity. Further understanding of the interplay between HCs/GJs and IGLDCPs would aid in identifying therapeutic targets that regulate the HC–Ig-like domain immune response, thereby providing a viable treatment strategy for immunological diseases. The present review delineates the clinical immunology-related applications of HC–Ig-like domain cross-activation, which would greatly benefit medical professionals and immunological researchers alike. HCs/GJs and IGLDCPs mediate phagocytosis via ATP; “eat me and don’t eat me” signals trigger innate immunity; HC-mediated trogocytosis promotes antigen presentation and amplification in innate–adaptive immunity; HCs also mediate non-specific transcytosis of antibodies produced by mature B lymphocytes in adaptive immunity.